2015
DOI: 10.1177/070674371506000305
|View full text |Cite
|
Sign up to set email alerts
|

The National Trajectory Project of Individuals Found Not Criminally Responsible on Account of Mental Disorder in Canada. Part 2: The People behind the Label

Abstract: Objective: To examine the psychosocio-criminological characteristics of not criminally responsible on account of mental disorder (NCRMD)–accused people and compare them across the 3 most populous provinces. In Canada, the number of people found NCRMD has risen during the past 20 years. The Criminal Code is federally legislated but provincially administered, and mental health services are provincially governed. Our study offers a rare opportunity to observe the characteristics and trajectories of NCRMD–accused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 12 publications
10
100
2
4
Order By: Relevance
“…Also, our study addressed files from 2000 to 2005; therefore, practices may have changed in recent years (e.g., as young mental health professionals enter the field we would expect to see shifts in practice reflecting research developments). Furthermore, there are differences across jurisdictions in the comprehensiveness of available information in the files (Crocker et al, in press‐b). We also did not consider the specific HCR‐20 items in the prediction model for dispositions, but rather the number of factors that were mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our study addressed files from 2000 to 2005; therefore, practices may have changed in recent years (e.g., as young mental health professionals enter the field we would expect to see shifts in practice reflecting research developments). Furthermore, there are differences across jurisdictions in the comprehensiveness of available information in the files (Crocker et al, in press‐b). We also did not consider the specific HCR‐20 items in the prediction model for dispositions, but rather the number of factors that were mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…The NTP (https://ntp-ptn.org, ) was an archival, longitudinal study examining a cohort of Canadian individuals found NCRMD in British Columbia (BC), Ontario (ON), and Québec (QC). The full methodology is described in detail by Crocker and colleagues (Crocker et al, ; see also Charette et al, ; Crocker et al, ; Crocker et al, 2015a–c; Nicholls et al, ; Salem et al, ; Wilson et al, ). Details relevant to the current analyses are presented here.…”
Section: Methodsmentioning
confidence: 99%
“…Our research revealed provincial differences in forensic patient characteristics. 4 It follows that the trajectories of people found NCRMD through the forensic mental health and RB systems may also vary from province to province. 5 …”
Section: Limitationsmentioning
confidence: 99%